Investigate the Effects of Formation Cutting Transportation in Inclined Wells to Prevent the Occurrence of Mechanical Stuck Pipes in an Iraqi Oilfield - Issa, Mustafa A.; Issa, Muntadher A.; Al-Zuobaidi, Ali A.; A. Alrazzaq, Ayad A. Alhaleem (Journal of Petroleum Research and Studies, 2025)
During drilling operations, cutting removal in deviated and vertical wells is one of the most significant challenges. It can cause high torque and drag, mud circulation loss, casing installation difficulties, poor cementing operations, and mechanical pipe sticking. These challenges can potentially increase non-productive time (NPT) and well costs. This study utilized Well Plan™ software to establish a hole-cleaning model for a specific well situated in the southern Iraqi oilfield. Thus, the minimum flow rate and cutting bed height necessary to ensure efficient cutting transportation from the borehole were calculated, resulting in the elimination or reduction of the mechanical pipe sticking problem. Subsequently, the influence of the drilling parameters on the removal of cuttings was examined by determining the minimum flow rate. The study’s findings indicate that there is a direct relationship between the minimum flow rate and certain drilling parameters, i.e., plastic viscosity, penetration rate, well inclination, and cutting density. While inverse relationship with other parameters, i.e., yield point, drilling mud weight, and rotation speed of drill string. Additionally, the minimum flow rate that is obtained from Well Plan™ software is greater than the actual flow rate. For instance, during the run-in hole where pipe stuck occurs in the Tanuma Formation, the actual flow rate was 713 gpm, while the minimum flow rate and the cutting bed height that are calculated from this model are 970 gpm and 1.77" respectively. Ultimately, the research findings can be utilized to financially support upcoming drilling operations in the surrounding area of the study.